Shifting aspect or elevation? The climate change response of ectotherms in a complex mountain topography. Issue 11 (26th August 2020) - Feldmeier, Stephan; Schmidt, Benedikt R.; Zimmermann, Niklaus E.; Veith, Michael; Ficetola, Gentile Francesco; Lötters, Stefan
Abstract: Aim: Climate change is expected to cause mountain species to shift their ranges to higher elevations. Due to the decreasing amounts of habitats with increasing elevation, such shifts are likely to increase their extinction risk. Heterogeneous mountain topography, however, may reduce this risk by providing microclimatic conditions that can buffer macroclimatic warming or provide nearby refugia. As aspect strongly influences the local microclimate, we here assess whether shifts from warm south‐exposed aspects to cool north‐exposed aspects in response to climate change can compensate for an upward shift into cooler elevations. Location: Switzerland, Swiss Alps. Methods: We built ensemble distribution models using high‐resolution climate data for two mountain‐dwelling viviparous ectotherms, the Alpine salamander and the Common lizard, and projected them into various future scenarios to gain insights into distributional changes. We further compared elevation and aspect (northness) of current and predicted future locations to analyse preferences and future shifts. Results: Future ranges were consistently decreasing for the lizard, but for the salamander they were highly variable, depending on the climate scenario and threshold rule. Aspect preferences were elevation‐dependent: warmer, south‐exposed microclimates were clearly preferred at higher compared to lower elevations. In terms of presence and future locations, we observed both elevational upward shifts and northward shifts in aspect. Under future conditions, the shift to cooler north‐exposed aspects was particularly pronounced at already warmer lower elevations. Main conclusions: For our study species, shifts in aspect and elevation are complementary strategies to mitigate climatic warming in the complex mountain topography. This complements the long‐standing view of elevational upward shift being their only option to move into areas with suitable future climate. High‐resolution climate data are critical in heterogeneous environments to identify microrefugia and thereby improving future impact assessments of climate change.